Prevalence of molar incisor hypomineralization (MIH) and its association with some risk factors in group of children attending two specialized dental centers in Erbil city - Dilan Yaseen Ismail; Sazan Sherdl Saleem (Erbil Dental Journal)
Background and objectives: Molar incisor hypomineralization (MIH) is frequent in children and the etiology is different. The study was conducted to determine the prevalence, and risk factors of MIH and to investigate the relationship between the severity of the defect in the teeth affected by MIH and the risk factors.